Pendidikan Kecakapan Hidup Berbasis Masjid untuk Mitigasi Kerentanan Sosial di Jembatan Wijaya Kusuma, Kediri - Masud, Ali; Izzuddin, Muhammad Andik; Yusuf, M. (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study aims to describe the practices, determinants of success, and the significance of implementing mosque-based life skills education at Nurul Huda Mosque in Mojo as a means to mitigate social vulnerability. To address these questions, the author employs a qualitative approach through a case study design. Data were collected using interviews, observation, and documentation techniques, and were then analyzed through a simultaneous cycle of data condensation, presentation, interpretation, and conclusion drawing. The findings indicate that the practice of mosque-based life skills education at Nurul Huda Mosque in Mojo is conducted in three stages: planning, implementation, and evaluation. Various life skills activities are organized, encompassing social and personal skills, academic and vocational skills, such as Gerakan Subuh Kubro (early morning congregation movement), Bocah Sarungan (a program for youth engagement), comparative studies with other mosques of similar identity, networking visits (silaturahmi/tabarruk-an) to the Kediri PCNU and East Java PWNU, large-scale religious gatherings (pengajian akbar), as well as training sessions in Quranic recitation, banjari (traditional Islamic music), screen printing, embroidery, tailoring, and mosque-related machinery. These activities are made possible by the innovation of the mosque management at Nurul Huda Mosque in Mojo and demonstrate significant effects on mitigating social vulnerability by adapting to the changing landscape around Wijaya Kusuma Bridge in Mojo, Kediri.